The Influence of Social Media Marketing and Product Quality on Purchase Decisions - Rosdiana Maharani; Nurul Qomariah; Arik Susbiyani; Ni Nyoman Putu Martini (Jurnal Penelitian IPTEKS, 2025)
Marketing management is a crucial aspect in the success of a company, it can attract customer purchasing decisions. Marketing management is the art and science of choosing target markets and building profitable relationships with them, which is done through effective and innovative marketing strategies. This study aims to determine the effect of social media marketing and product quality on purchasing decisions at PT Java Indosinergi Creative. This study is a quantitative study with a research population of PT Java Indosinergi Creative customers. The sample in this study amounted to 100 people. The data collection method used in this study was by distributing questionnaires online. Data analysis used descriptive statistics and inductive statistics. The results of the study showed that 1) social media marketing has a positive and significant effect on purchasing decisions, 2) product quality has a positive and significant effect on purchasing decisions. The results of this study have implications for developments related to purchasing decisions that can increase due to social media marketing and also the good quality of the products produced.